The Silence of the Subaltern in the Partition of India: Bengali Gendered Trauma Narratives in Shobha Rao’s “The Lost Ribbon” and Ramapada Chaudhuri’s “Embrace” - Dolors Ortega Arévalo (Universitat Autònoma de Barcelona, 2021)
The Partition of India was one of the crucial moments marking the transition between the colonial and postcolonial era. Partition has become ever since a long-term process that continues to elicit political, cultural and emotional contexts in South Asia. The creation of Pakistan as a homeland for South Asian Muslims involved the division of Bengal and Punjab along religious lines and while the celebratory narratives of decolonization and nationhood marked the official historiographies of 1947, trauma, loss and displacement were not part of the narrative.   The following article focuses on the experience of abducted women in Bengal in the communal riots during the Partition of India. This analysis stems from a brief overview of the silence that has permeated the partition of Bengal within historiography and the scarce literary response that has articulated those silences. It moves on to the analysis of the violence that abducted women suffered in this context. Finally, it deals with two short stories, “The Lost Ribbon” and “Embrace,” which situate gender trauma narratives by showing two radically different responses to the event of becoming a mother of an abductor’s child on the other side of the border and the effect that displacement and forced repatriation has upon female bodies.